To study the work design of a small manufacturing industry in order to improve its productivity / Azli Mohamed and Zuraimi Borhan - Mohamed, Azli; Borhan, Zuraimi (2001)
This project is basically to study the work design in a small manufacturing industry which includes flow process, bar chart, work sampling, standard time, material handling, health and safety, and job design. Data that were collected from observation and information provided by the company give some guidelines to improve the company's productivity. In this study, various considerations had been taken in order to achieve an optimal solution to the problems. This report had shown the method on how to apply work design concept into actual production at the company. Conclusions are presented with the view of conforming the objective of this study. There are four phases of study which have been done in the production line which include study of the existing conditions and related problems. This report provides a case study, which gives some recommendations on how to improve the company's productivity and efficiency in the production line.